Tingkat Kemampuan Passing Bawah Bola Voli (Survei pada UKM Bola Voli Universitas Muhammadiyah Surakarta) - Maulaya, Dinda Suci; Jariono, Gatot; Nurhidayat, Nurhidayat (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the level of underhand passing ability among members of the Volleyball Student Activity Unit (UKM) at Muhammadiyah University of Surakarta. This research uses a descriptive quantitative method with a survey approach, where data were collected through underhand passing tests using the Brumbach Forearms Pass-wall Volley instrument. The sample consists of 24 randomly selected members of the volleyball UKM at Muhammadiyah University of Surakarta, comprising 12 males and 12 females. The results show that most members fall into the “Good” category, with the highest percentage of “Good” found among males (50%) and females (41.7%). The study results indicate that the underhand passing ability test results among UKM volleyball members are categorized as follows: 6 individuals (25%) in Very Good, 11 individuals (45.83%) in Good, 6 individuals (25%) in Fair, 1 individual (4.17%) in Poor, and 0 individuals (0%) in Very Poor. The conclusion indicates that the underhand passing ability level of the volleyball UKM members at Muhammadiyah University of Surakarta is categorized as Good. Keyword: Survey, Skill, Forearms Passing Volley, Student Activity Unit